Substituted 1-(isoxazol-3-yl)methyl-1H-1, 2, 3-triazoles: Synthesis, palladium(II) complexes, and high-turnover catalysis in aqueous media. Issue 27 (5th July 2018) - Bumagin, Nikolay A.; Kletskov, Alexey V.; Petkevich, Sergey K.; Kolesnik, Iryna A.; Lyakhov, Alexander S.; Ivashkevich, Ludmila S.; Baranovsky, Alexander V.; Kurman, Peter V.; Potkin, Vladimir I.
Abstract: New substituted 3-((1H-1, 2, 3-triazol-1-yl)methyl)-5-arylisoxazoles (aryl = Ph, p -Tol) and 2-(5-phenylisoxazol-3-yl)-5-(2-(1-((5-( p -tolyl)isoxazol-3-yl)methyl)-1H-1, 2, 3-triazol-4-yl)ethyl)-1, 3, 4-oxadiazole were synthesized by means of click-chemistry procedures. The obtained compounds were used as ligands in preparation of palladium(II) complexes, and the latter proved to be high-turnover-number catalysts for CC cross-coupling reactions under Green Chemistry conditions. One of the ligands was structurally characterized by single crystal X-ray diffraction, and the structure of complexes was determined by 1 H, 13 C, 15 N NMR spectroscopy and quantum-chemical modeling. Graphical abstract: Image 1